Does Career Risk Deter Potential Entrepreneurs?. (21st September 2021) - Gottlieb, Joshua D; Townsend, Richard R; Xu, Ting
Abstract: Do potential entrepreneurs remain in wage employment because of concerns that they will face worse job opportunities should their entrepreneurial ventures fail? Using a Canadian reform that extends job-protected leave to one year for women giving birth after a cutoff date, we study whether the option to return to a previous job increases entrepreneurship. A regression discontinuity design reveals that a longer job-protected leave increases entrepreneurship by 1.9 percentage points. These entrepreneurs start incorporated businesses that hire employees, in industries in which experimentation before entry has low costs and high benefits. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.